The „Third Wave“ of Democratization (Czech Journal of International Relations, 1998)
Larry Diamond, Marc F. Plattner , Yun-han Chu and Hung-mao Tien (eds.): Consolidating the Third Wave Democracies. Regional Challenges. Baltimore and London 1997, 333 stran.